# From the common equilibrium point of view

1. Dec 18, 2003

### deda

The basic rule of lever claims:
Fm1 * Dm1 = Fm2 * Dm2 and
Fm1 * Md2 = Fm2 * Md1 which results in
Md1 * Dm1 = Md2 * Dm2
where Md is an equilibrium mass in geometrical space and
Dm is an equilibrium distance in gravitation space.

and

Fq1 * Dq1 = Fq2 * Dq2 and
Fq1 * Qd2 = -Fq2 * Qd1 which results in
Qd1 * Dq1 = -Qd2 * Dq2
where Qd is an equilibrium charge in geometrical space and
Dq is an equilibrium distance in electrical space.

also

Gq1 * Mq1 = Gq2 * Mq2 and
Gq1 * Qm2 = -Gq2 * Qm1 which results in
Mq1 * Qm1 = -Mq2 * Qm2
where Mq is an equilibrium mass in electrical space and
Qm is an equilibrium charge in gravitation space.

If we review all the distances from common eqiulibrium point then:
we have the system of following equations:
D1 * M1 = D2 * M2 and
M1 * Q1 = -M2 * Q2 and
Q1 * D1 = -Q2 * D2

The product of all left sides = to the product of all right sides so
D1^2 * M1^2 * Q1^2 = D2^2 * M2^2 * Q2^2 finding the square root yields

D1 * M1 * Q1 = -D2 * M2 * Q2

where if (D1,M1,Q1) is matter particle then (D2,M2,Q2) is its balancing antimatter particle and D,M,Q are distance, mass and charge regarding same equilibrium point.

Impresive A?